Pengaruh Kepercayaan, Kualitas E-Commerce, Dan Pengalaman Berbelanja Terhadap Minat Beli Ulang Konsumen Melalui Situs Belanja Online Tokopedia (Studi Kasus Pada Mahasiswa FEB Angkatan 19 UM Metro) - Japlani, Ardiansyah; Septiana, Nani; Pertiwi, Nabila Citra (Jurnal Manajemen DIVERSIFIKASI, 2023)
The development of an increasingly modern world is always followed by the sophistication ofinternet-based information technology that can be used to process data including processing,obtaining, compiling, and storing data from various ways to produce quality informationwith relevant, accurate, and timely information. In trading, one of them is the marketplace.One of the well-known marketplaces and always the best rating is Tokopedia. This study aimsto determine the effect of trust, e-commerce quality and shopping experience, on repurchaseinterest on the Tokopedia online site. The sample of this research is the students of Feb 19Universitas Muhammmadiyah Metro. The research design is quantitative research. Themethod used in this research is a survey approach. The population and sample of the studywere students of the management study program, Faculty of Economics and Business,University of Muhammadiyah Metro, class of 2019 with a total sample of 69 students. Datacollection techniques using a questionnaire. The analytical tool used is quality analysis andmultiple regression analysis. The results show that trust, e-commerce quality, and shoppingexperience partially or simultaneously have a positive and significant effect on repurchaseinterest in management study program students using the Tokopedia site at MuhammadiyahMetro University.